PELANGGARAN PRINSIP KERJA SAMA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMK BATIK 1 SURAKARTA - Fasha Nabilah Aprilliani; Muhammad Rohmadi; Atikah Anindyarini (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purpose of this research is to explain and describe (1) a form of violation of the principle of cooperation in the interaction of learning Indonesian in SMK Batik 1 Surakarta; (2) the purpose of violating the principle of cooperation in learning Indonesian in SMK Batik 1 Surakarta; (3) the function of violating the principle of cooperation in the interaction of learning Indonesian in SMK Batik 1 Surakarta. This research is descriptive qualitative research with main data source that is recording of learning activity of Indonesia in class X Visual Communication Design and XI Marketing. Technique of data retrieval in this research use observation technique and deep interview technique. Technique of taking research subject using purposive sampling technique. The data validity test used is triangulation technique and triangulation theory. Data analysis techniques using interactive analysis techniques. Based on the results of the research, found a speech breaking a maximum of cooperation and speech principles that violate two maxims of cooperation principles, called a single maximal offense and a double maximal offense.  Violation of maxim that happened not only done by teacher but also done by student. Maximum violations have 11 violation objectives. Maximum violation of the principle of cooperation done by both students and teachers have their respective functions. The function of language related to maximal violation have 7 functions.